THE EFFECT OF WORK STRESS AND FAMILY-JOB CONFLICT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT PT. JTRUST OLYIMPINDO MULTI FINANCE, INDONESIA - Bugis, Meili (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyse the effect of work stress and family-job conflict on job satisfaction and its implications for employee performance, both directly and indirectly through job satisfaction as a mediating variable. A quantitative approach was used, with data collected through questionnaires distributed to respondents. Data analysis was performed using inferential statistical methods, including t-tests, to test the formulated hypotheses. The results showed that work stress had a significant, adverse effect on job satisfaction, indicating that increased work pressure can reduce employee satisfaction. Meanwhile, family-work conflict on job satisfaction, job satisfaction on performance, and work stress on performance showed no significant effects. However, work-family conflict was found to have a substantial impact on employee performance, indicating that an imbalance between work and family demands can interfere with work productivity. In addition, the indirect effect of work stress and work-family conflict on performance via job satisfaction was accepted but was not significant. These findings indicate that job satisfaction is not yet fully capable of acting as a potent mediator. Overall, this study emphasises the importance of managing work stress and role conflict to improve employee well-being and performance sustainably.